Proton-Gradient-Driven Oriented Motion of Nanodiamonds Grafted to Graphene by Dynamic Covalent Bonds - Kovaříček, Petr; Cebecauer, Marek; Neburková, Jitka; Bartoň, Jan; Fridrichová, Michaela; Drogowska, Karolina A; Cigler, Petr; Lehn, Jean-Marie; Kalbac, Martin (ACS nano, 2018)
Manipulating nanoscopic objects by external stimuli is the cornerstone of nanoscience. Here, we report the implementation of dynamic covalent chemistry in the reversible binding and directional motion of fluorescent nanodiamond particles at a functionalized graphene surface via imine linkages. The dynamic connections allow for controlling the formation and rupture of these linkages by external stimuli. By introduction of pH gradients, the nanoparticles are driven to move along the gradient due to the different rates of the imine condensation and hydrolysis in the two environments. The multivalent nature of the particle-to-surface connection ensures that particles remain attached to the surface, whereas its dynamic character allows for exchange reaction, thus leading to displacement yet bound behavior in two-dimensional space. These results open a pathway for thermodynamically controlled manipulation of objects on the nanoscale.
Keywords: directional nanoparticle motion; 2D materials; dynamic covalent chemistry; fluorescent nanodiamonds; graphene functionalization